Development and evaluation of a novel series of Nitroxoline-derived BET inhibitors with antitumor activity in renal cell carcinoma. (November 2018) - Chen, Wei; Zhang, Hao; Chen, Zhifeng; Jiang, Hao; Liao, Liping; Fan, Shijie; Xing, Jing; Xie, Yiqian; Chen, Shijie; Ding, Hong; Chen, Kaixian; Jiang, Hualiang; et al.
Abstract Small molecular inhibitors targeting BRD4 family proteins are emerging as promising therapies in many types of human malignancies. However, whether BRD4, as well as other BET family members, may serve as therapeutic targets in renal cell carcinoma (RCC) remains unknown. In this study, we found that both BRD2 and BRD4 were over-expressed in RCC tissues, knock-down both of which achieved potent anti-proliferative effects in RCC cells. A novel category of BET inhibitors, originated from an approved drug Nitroxoline, were synthesized and evaluated with biochemical and cellular assays, as well as the method of crystallography. The complex crystal structures of several compounds in this category with the first bromodomain of BRD4 (BRD4-BD1) were solved, revealing the binding mechanism and facilitating further structural optimizations. Among them, compound BDF-1253 showed an approximately four-fold improvement in BRD4 inhibition compared with the prototype Nitroxoline and had good selectivity for BET proteins against other bromodomain proteins or epi-enzymes in biochemical assays. Compound BDF-1253 efficiently suppressed the expression of BET downstream genes, impaired RCC cells viability via inducing cell cycle arrest and apoptosis, and decreased tumor growth in RCC xenografts. In summary, these results suggest that inhibition of BET family members has great therapeutic potentials in the treatment of RCC, and the novel series of BET inhibitors reported here are promising to become RCC drug candidates.